1997
DOI: 10.1002/cjce.5450750617
|View full text |Cite
|
Sign up to set email alerts
|

Corresponding‐states and parachor models for the calculation of interfacial tensions

Abstract: A generalized corresponding-states model based on two reference fluids and a parachor correlation were developed for the prediction of interfacial tensions for non-polar and weakly polar pure fluids and mixtures. Pure methane and n-octane were chosen as reference fluids of the corresponding-states model. The two models were tested on 86 pure substances, more than 30 binary and multicomponent mixtures, 1 1 naphtha reformate cuts, 6 petroleum cuts and 2 North Sea oil mixtures. The calculated results were found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 34 publications
1
61
0
Order By: Relevance
“…Despite its empirical basis, Fowler 18 showed that the relation can be derived as an explicit function of the intermolecular potential in the case of a step-wise density profile, which is a reasonable assumption far away from the critical point. Other popular approaches are based on the corresponding-states principle of Guggenheim 19 , where empirical relations can be developed in terms of a specific reference fluid to provide an accurate representation of the surface tension 20 . Though useful in correlating data for the interfacial tension of fluid mixtures, these empirical relations offer little in way of predictive capability.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its empirical basis, Fowler 18 showed that the relation can be derived as an explicit function of the intermolecular potential in the case of a step-wise density profile, which is a reasonable assumption far away from the critical point. Other popular approaches are based on the corresponding-states principle of Guggenheim 19 , where empirical relations can be developed in terms of a specific reference fluid to provide an accurate representation of the surface tension 20 . Though useful in correlating data for the interfacial tension of fluid mixtures, these empirical relations offer little in way of predictive capability.…”
Section: Introductionmentioning
confidence: 99%
“…The application of corresponding-states models extends from equilibrium properties such as vapor pressure [24][25][26][27][28], liquid density [11,26,[28][29][30], or surface tension [12,13,15,16,26,31,32] to transport properties such as viscosity [11,26,[33][34][35][36] and thermal conductivity [14,26,[37][38][39].…”
Section: Corresponding-states Principlementioning
confidence: 99%
“…The application of corresponding states models extends from equilibrium properties such as vapor pressure [12][13][14][15][16], liquid density [14,[16][17][18], or surface tension [4,5,14,19,20] to transport properties such as viscosity [2,14,[21][22][23][24] and thermal conductivity [14,[25][26][27].…”
Section: Corresponding States Principlementioning
confidence: 99%